The Decline of Thai Private Higher Education - Praphamontripon, Prachayani (International Higher Education, 2010)
Though Thai private higher education expanded during the 1990s, the private higher education sector has experienced stagnant and declining enrollment since 2002. While private higher education leaders speculate that public expansion and public privatization are the main factors for their declining market share, their public counterparts argue that such a drop mainly involves the country's shifting demographics.